Adipocyte fatty acid binding protein levels in patients with coronary artery disease and its relationship to alternative biomarkers - Kaman, Dilara; Ilhan, Necip; Akbulut, Mehmet (Via Medica, 2015)
Background and aim: An association between circulating adipocyte fatty acid-binding protein (A-FABP) levels and coronary artery disease (CAD) has been reported. In this case-control study, we investigated the relationship between plasma levels of A-FABP and the severity of CAD in Turkish subjects. We also assessed its relationship to alternative biomarkers. Methods: Two hundred and eighty patients undergoing coronary angiography were enrolled in the study. By means of coronary angiography, the study population was divided into subjects without any angiographically detectable CAD (no vessel disease; n = 88) and individuals with single-vessel disease (n = 65), or double-or triple-vessel disease (n = 127). Lipid concentrations were measured by an autoanalyser and A-FABP, lipoprotein associated phospholipase A(2) (Lp-PLA(2)), oxidised-low density lipoprotein (ox-LDL) and high-sensitivity C-reactive protein (hsCRP) levels by a commercial enzyme-linked immunosorbent assay (ELISA) kit. Results: In our study population, total cholesterol and LDL cholesterol levels did not differ significantly between the groups. Levels of high density lipoprotein cholesterol, A-FABP, Lp-PLA(2), ox-LDL and hsCRP were significantly different among groups. The higher levels of A-FABP, Lp-PLA(2), ox-LDL and hsCRP levels were shown in patients with double/triple-vessel disease. There was not a significant correlation between A-FABP and other biomarkers in CAD patients. Conclusions: Initially, plasma levels of A-FABP were significantly elevated in CAD patients with double/triple-vessel disease. Our results demonstrated alterations in A-FABP levels with severity of CAD and, therefore, indirectly support the hypothesis of an active role for A-FABP in the pathogenesis of CAD.
Keywords: adipocyte fatty acid-binding protein (A-FABP); coronary artery disease; lipoprotein associated phospholipase A(2) (Lp-PLA(2)); oxidised-low density lipoprotein (ox-LDL); high-sensitivity C-reactive protein (hsCRP)